HER2 Reactivity Pattern and Association with Various Tumor Factors in Breast Cancer Patients - George, Greeshma Ann; Antony, Philips (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Breast cancer prognosis and therapeutic strategies are strongly influenced by biomarker profiles, particularly HER2 reactivity, which impacts treatment selection and disease progression.Objective: To study the HER2 reactivity pattern and identify the association of HER2 pattern with various tumor factors in patients with breast cancer.Methods: This prospective study comprised of 150 surgically operated female cases of breast cancer admitted to the Department of Pathology for ER, PR, and HER2 testing between December 2015 and October 2017.Results: Of 150 cases, the mean age was 52 years (IQR, 41-63 years). This study showed that majority of tumors were IDC-NOS, grade 2, tumor size T2, and had negative lymph node status. HER2 negative cases were in the majority, as well as the ER/PR+ cases. Triple-negative cases were slightly higher (49 cases). When HER2 was correlated with tumor characteristics, younger patients with HER2-positive were in the majority, with the higher the tumor size is, the greater the chance for HER2 negativity. The majority of IDC cases and all ILC cases showed HER2 negativity. Both medullary cases showed HER2 positive, and one case of mucinous showed HER2 negativity with ER/PR positivity. Irrespective of ER/PR status, the majority of tumors had HER2 negativity.Conclusion: HER2/neu positively correlates with increasing age, menstrual status, tumor size, and tumor grade. No association is found between histological type, lymph node status, and ER/PR. This study also reveals that patient with higher levels of HER2/NEU-overexpression had statistically significant lower levels of ER/PR-positive tumors. In addition, when Her2 neu is positive in tumors, along with ER and PR, it is mostly high-grade.